2001
DOI: 10.1002/1522-2675(20010919)84:9<2550::aid-hlca2550>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyte Addition on the Colloidal Stability of Aqueous Zeolite Sols

Abstract: Dedicated to Professor Andre M. Braun on the occasion of his 60th birthday Recovery of zeolites from aqueous media can be a very difficult operation, when the crystals have colloidal dimensions. The solid-liquid separation can be facilitated by processing at the respective isoelectric point (IEP) where the sol is unstable and the crystals form aggregates. The addition of salts results in a further improvement, because the zeolite agglomerates become larger, and the pH range of flocculation is broadened. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 2 publications
3
16
0
Order By: Relevance
“…2 show that the zeolite 13X particles have an isoelectric point (IEP) at pH 4.7. Previous work has shown that the IEP of zeolites depends on the elemental composition 34 . The reduction in the IEP of MFI zeolite with the increasing aluminum content was related to the higher acid strength for Al‐containing surfaces compared with silicalite crystal surfaces 34,35 .…”
Section: Resultsmentioning
confidence: 69%
“…2 show that the zeolite 13X particles have an isoelectric point (IEP) at pH 4.7. Previous work has shown that the IEP of zeolites depends on the elemental composition 34 . The reduction in the IEP of MFI zeolite with the increasing aluminum content was related to the higher acid strength for Al‐containing surfaces compared with silicalite crystal surfaces 34,35 .…”
Section: Resultsmentioning
confidence: 69%
“…We have shown recently that it is possible to control the agglomeration and peptisation of such colloidal zeolites in aqueous media [10]. This is a prerequisite for their efficient solidliquid separation [11,12], and for the manufacturing of catalysts containing small zeolite crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The zeta potential of the precipitated barium sulfate in the 50 presence of 2 (0.0134 mM) was measured at -17mV, which, while being slightly negative, it is still within the range of zeta potentials (±30mV) where the system is expected to be unstable and would spontaneously coagulate. 10 Thus, charge stabilization is unlikely to be a factor in barite mesocrystal formation in the 55 presence of 2. Stabilization of some kind must be operating in order to avoid random aggregative processes.…”
mentioning
confidence: 99%